Rapid shifts in distribution and high‐latitude persistence of oceanographic habitat revealed using citizen science data from a climate change hotspot. (1st August 2018) - Champion, Curtis; Hobday, Alistair J.; Tracey, Sean R.; Pecl, Gretta T.
Abstract: The environmental effects of climate change are predicted to cause distribution shifts in many marine taxa, yet data are often difficult to collect. Quantifying and monitoring species' suitable environmental habitats is a pragmatic approach for assessing changes in species distributions but is underdeveloped for quantifying climate change induced range shifts in marine systems. Specifically, habitat predictions present opportunities for quantifying spatiotemporal distribution changes while accounting for sources of natural climate variation. Here we demonstrate the utility of a marine‐based habitat model parameterized using citizen science data and remotely sensed environmental covariates for quantifying shifts in oceanographic habitat suitability over 22 years for a coastal‐pelagic fish species in a climate change hotspot. Our analyses account for the effects of natural intra‐ and interannual climate variability to reveal rapid poleward shifts in core (94.4 km/decade) and poleward edge (108.8 km/decade) oceanographic habitats. Temporal persistence of suitable oceanographic habitat at high latitudes also increased by approximately 3 months over the study period. Our approach demonstrates how marine citizen science data can be used to quantify range shifts, but necessitates shifting focus from species distributions directly, to the distribution of species' environmental habitat preferences. Abstract : The environmental effects of climate change are predicted to cause distribution shifts in many marine taxa, yet data required to analyse these shifts are often difficult to collect. In this study, we utilize increasingly available citizen science data to parametrize a habitat suitability model for a typical coastal‐pelagic species (kingfish; Seriola lalandi) within a global marine hotspot. We then demonstrate the utility of spatial habitat predictions for quantifying climate‐driven distribution shifts while accounting for oft‐ignored intra‐ and interannual climate variability. Our approach highlights the value of marine citizen science data for quantifying range shifts, but necessitates shifting focus from species distributions directly, to the distribution of species' environmental habitat preferences.